Responding to learner diversity and learning difficulties - Conrad, Dennis A.; Blackman, Stacey N. J. (Caribbean discourse in inclusive education (Series), 2018)
Caribbean Discourse in Inclusive Education Volume II "Responding to Learner Diversity and Learner Difficulties" shares selected critical reflections and recommendations on the way educational communities respond to student diversity and difficulties learning. These contexts include the Caribbean, the Diaspora, and beyond. Authors explore issues and strategies for realizing and sustaining the agenda of education for all within primarily, but not limited to, the Caribbean. While the authors are aware of the ongoing debate between the terms 'education for all' and 'inclusive education', we use these terms interchangeably. We hold the position that inclusive education is about commitment to removing barriers to optimum learning for all learners regardless of age, ability, ethnicity, gender, geography, race, religion, sexual orientation or other differences. 'Responding to Learner Diversity and Difficulties' extend the discourse to include stakeholders committed to sharing their experiences and strategies for overcoming barriers to inclusive education.This second volume presents research that examines how teachers can respond to students with disabilities and difficulties learning, teach challenging curriculum content in mathematics and literacy, build citizenship through student voice, improve teacher practice via co-teaching and critical reflection, promote inclusive practice through leadership and advocacy. It can be used as a core text or companion reader for students at the undergraduate and graduate levels, lecturers, practitioners, researchers and policy makers.